Laser vs bur for bone cutting in impacted mandibular third molar surgery: A randomized controlled trial - Deepak Passi; Uma Shankar Pal; Shadab Mohammad; Rakesh Kumar Singh; Divya Mehrotra; Geeta Singh; Manoj Kumar; Arul A.L. Chellappa; Chandan Gupta (Elsevier, 2013)
Background: The aim of this study was to assess the feasibility of Er: YAG laser in bone cutting for removal of impacted lower third molar teeth and compare its outcomes with that of surgical bur. Materials & methods: The study comprised 40 subjects requiring removal of impacted mandibular third molar, randomly categorized into two equal groups of 20 each, who had their impacted third molar removed either using Er: YAG laser or surgical bur as per their group, using standard methodology of extraction of impacted teeth. Clinical parameters like pain, bleeding, time taken for bone cutting, postoperative swelling, trismus, wound healing and complications were compared for both groups. Observation & result: Clinical parameters like pain, bleeding and swelling were lower in laser group than bur group, although the difference was statistically not significant. However, postoperative swelling showed significant difference in the two groups. Laser group required almost double the time taken for bone cutting with bur. Trismus persisted for a longer period in laser group. Wound healing and complications were assessed clinically and there was no significant difference in both the groups. Conclusion: Based on the results of our study, the possibility of bone cutting using lasers is pursued, the osteotomy is easily performed and the technique is better suited to minimally invasive surgical procedures. The use of Er: YAG laser may be considered as an alternative tool to surgical bur, specially in anxious patients.